Living better with energy - Programa Alianza en Energía y Ambiente con la Región Andina (AEA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
Experiences with renewable energies to promote the social development in the Andean Region. Projects described in this documentary video are being supported by the Energy and Environment Partnership Programme with the Andean Region (EEP) with the financial support of the Ministry for Foreign Affairs of Finland, inside the framework of the cooperation for development through the Inter-American Institute for Cooperation on Agriculture (IICA)